Search for neutral long-lived particles in pp collisions at s $$ \sqrt{s} $$ = 13 TeV that decay into displaced hadronic jets in the ATLAS calorimeter. (Tufts University. Tisch Library., 2022)
Keywords : Hadron-Hadron Scattering.; Springer Open.